(3x+5)/(4x+5)=2/3

Simple and best practice solution for (3x+5)/(4x+5)=2/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+5)/(4x+5)=2/3 equation:



(3x+5)/(4x+5)=2/3
We move all terms to the left:
(3x+5)/(4x+5)-(2/3)=0
Domain of the equation: (4x+5)!=0
We move all terms containing x to the left, all other terms to the right
4x!=-5
x!=-5/4
x!=-1+1/4
x∈R
We add all the numbers together, and all the variables
(3x+5)/(4x+5)-(+2/3)=0
We get rid of parentheses
(3x+5)/(4x+5)-2/3=0
We calculate fractions
(9x+15)/(12x+15)+(-8x-10)/(12x+15)=0
We multiply all the terms by the denominator
(9x+15)+(-8x-10)=0
We get rid of parentheses
9x-8x+15-10=0
We add all the numbers together, and all the variables
x+5=0
We move all terms containing x to the left, all other terms to the right
x=-5

See similar equations:

| 4+3y/6y-2=-3/5 | | (〖4D〗^4-〖8D〗^3〖-7D〗^2+11D+6)y=0 | | -7=7y+28 | | 4x-6=5(x-7) | | 144/4=n/6 | | (3x+5)/(4x+6)=5/4 | | (2x-1)-5=4x | | x^2+6x+3=-5 | | (6-2x)=-23 | | n^2+6n+3=-5 | | (6-2x)=23 | | 2x/3=4x | | 2.5/5=n/3 | | 5p+16=6 | | (2-3x)-1=0 | | 6(y-2)-3(y+3)-5(y+3)=0 | | 2x+38=3x-26 | | (x-7)+(x+1)=0 | | (-6-5x)=-61 | | (x+3)-(x-2)=4 | | 8+11n=14n–7 | | (x*61)*3.6=43.92 | | x/183=0.24 | | (-6-5x)=61 | | (7x+4)/2x=8 | | (5x)3=30 | | 16=4(z-5) | | 3(t-4)+8=14 | | 3t-4+8=14 | | 6=5u-u^ | | b/8+8=15 | | 7-5t=-6t |

Equations solver categories